Utilization of adolescent friendly health services and its associated factors among higher secondary students in mid-western Himalayan mountainous district of Nepal - Mahesh Sharma; Bijay Khatri; Archana Amatya; Narayan Subedi; Dipak Prasad Upadhyaya; Bhim Prasad Sapkota; Parvati Bista (Public Library of Science (PLoS), 2023)
Adolescent friendly health services (AFHS) are designed to make health services accommodate the unique needs of adolescents. AFHS are characterized by three basic characteristics (programmatic, health facilities and health service providers) that should be applied. However, limited is known about the use of AFHS in the context of Nepal. This study aimed to assess the extent of AFHS utilization and associated factors among higher secondary students in the Jumla district of Nepal. A cross-sectional quantitative study was conducted in October-November 2017. Data were collected from a random sample of 528 aged 16-19 years old using a self-administered survey in their classroom. Adjusted Odds Ratios (AOR) and a 95% confidence level were estimated to measure the strength of association between the outcome variable (utilization of AFHS) and independent variable using multivariable logistic regression. Knowledge related to AFHS, measured by a seven-item scale, was based on information about the availability of AFHS. More than two-thirds (67.05%) of adolescents had utilized AFHS at least once in the last twelve months before the survey. In multivariable logistic regression analysis, knowledge level [AOR = 14.796, 95%CI (5.326-41.099)], cost of services [AOR = 2.971, 95%CI (1.764-5.003)], satisfaction from services [AOR = 1.817, 95%CI (1.037-3.185)] and availability of waiting room [AOR = 1.897, 95%CI (1.096-3.283)] were significantly associated with the utilization of AFHS. The utilization of AFHS was less than the country's target of universal utilization in this study. Adolescents' knowledge level about AFHS was importantly associated with its utilization. Utilization increases with lower service costs, client satisfaction, and availability of waiting rooms in the health facility. The health planners should make efforts to create a conducive environment for the adolescent by training the AFHS providers, particularly those who work in government institutions, and strengthening the awareness creation strategies among adolescents to increase the utilization of the services.